Mixed ionic-electronic conduction in K1/2Bi1/2TiO3 - Li, Linhao; Li, Ming; Reaney, Ian M.; Sinclair, Derek C. (Royal Society of Chemistry, 2017)
Recently, it has been reported that the Pb-free piezoelectric perovskite Na1/2Bi1/2TiO3 (NBT) can be compositionally tuned by close control of the A-site starting stoichiometry to exhibit high levels of oxide-ion conduction. The related K1/2Bi1/2TiO3 (KBT) perovskite has also drawn considerable interest as a promising Pb-free piezoelectric material; however, its conduction properties have been less extensively investigated. Here we report on the influence of the K/Bi ratio in the starting composition on the electrical properties using a combination of impedance spectroscopy and ion-transport property measurements. KBT ceramics exhibit mixed ionic-electronic (oxide-ion) conduction with tion similar 0.5 at 600-800 degreeC and although variations in the A-site starting stoichiometry can create a similar1 order of magnitude difference in the bulk conductivity at >500 degree C, the conductivity is low (ca. 0.1 to 1 mS cm-1 at 700 degree C) and the activation energy for bulk conduction remains in the range similar1.2 to 1.5 eV. The high temperature electrical transport properties of KBT are therefore much less sensitive to the starting A-site stoichiometry as compared to NBT. However, KBT ceramics exhibit non-negligible proton conduction at lower temperatures (<300 degree C). For K/Bi greater-than-or-equal 1 the total conductivity of KBT ceramics at room temperature can be as high as similar0.1 mS cm-1 under wet atmospheric conditions. This study demonstrates ionic conduction to be a common feature in A1/2Bi1/2TiO3 perovskites, where A = Na, K.